Estimation on Achievable Parameter Regime of Warm Dense Matter Generated by Isochoric Heating Discharge using Intense Pulsed Power Generator. (March 2016) - Hayashi, Ryota; Kashine, Kenji; Tokuchi, Akira; Tamura, Fumihiro; Watabe, Arata; Kudo, Takahiro; Takahashi, Kazumasa; Sasaki, Toru; Kikuchi, Takashi; Aso, Tsukasa; Harada, Nob.; Jiang, Weihua
Abstract: An evaluation method for warm dense matter (WDM) with similar timescale in inertial confinement fusion (ICF) by isochoric heating using intense pulsed power generator ETIGO-II is considered for evaluating target behavior. The temperature increase of the sample is estimated from the numerical calculation using the measured current. As a result, in the case that the shape of sample is ϕ 2 mm x 10 mm and the density is 0.01 times solid density of copper, the temperature of sample increases up to 30000 K. It is expected that the WDM is generated using the proposed method with ICF implosion timescale.